Microporous carbon from a biological waste-stiff silkworm for capacitive energy storage - Gong, Chengcheng; Wang, Xinzhu; Ma, Danhua; Chen, Huifeng; Zhang, Shanshan; Liao, Zhixin (Electrochimica acta, 2016)
In general, carbon materials with high specific surface area (SSA), well-balanced pore size distributions, and appropriate content of heteroatom functionalities are essential to enhance the performance of electric double layer capacitors (EDLCs) for capacitive energy storage. In this study, a low-cost biological waste-stiff silkworm was first used as precursor for the synthesis of well-developed microporous carbon (SSMC) material by simple steps of carbonization and further activation. The SSMC was endowed with ultra-high SSA (2523m2g−1), large pore volume (1.37m3g−1), and high content of heteroatom functionalities (∼3.5 at% N and ∼5.1 at% O). EDLCs employed SSMC as active material showed high specific capacitance of 304Fg−1 and 256Fg−1 at current densities of 1Ag−1 and 20Ag−1, respectively, suggesting the good rate capability. Symmetric-two-electrode test in aqueous electrolyte also delivered the specific capacitance of 235Fg−1 with the energy density of ∼7.9Whkg−1. The findings confirmed the feasible way that using the eco-friendly biomass raw material to construct high performance capacitive energy storage device.